2022
DOI: 10.3390/s22239470
|View full text |Cite
|
Sign up to set email alerts
|

Photostability Enhancement of Dual-Luminophore Pressure-Sensitive Paint by Adding Antioxidants

Abstract: Antioxidants were applied to a dual-luminophore pressure-sensitive paint (PSP), and the effects on photodegradation caused by exposure to excitation light were studied. Three types of antioxidants that are commonly used for the photostability enhancement of polymers were added to a dual-luminophore PSP, and degradation rates and pressure/temperature sensitivities were investigated by coupon-based tests. One-hour-long aging tests were performed in a pressure chamber with a continuous excitation light source und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…This study showed that this alternative solution is more effective. In addition, the introduction of temperature-sensitive luminophore in fast PSPs usually causes severe photodegradation and non-uniformity due to the photochemical interaction between luminophores [27][28][29]. A possible solution is to physically separate two luminophores [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that this alternative solution is more effective. In addition, the introduction of temperature-sensitive luminophore in fast PSPs usually causes severe photodegradation and non-uniformity due to the photochemical interaction between luminophores [27][28][29]. A possible solution is to physically separate two luminophores [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%